2008
DOI: 10.1063/1.2994732
|View full text |Cite
|
Sign up to set email alerts
|

A quantum chemical study of H2S2: Intramolecular torsional mode and intermolecular interactions with rare gases

Abstract: The structural and energetic properties of the H 2 S 2 molecule have been studied using density functional theory, second-order Møller-Plesset method, and coupled cluster theory with several basis sets. In order to extend previous work on intra-and intermolecular dynamics of the chirality changing modes for H 2 O 2 and its derivatives, our focus has been on the torsion around the S-S bond, along with an extensive characterization of the intermolecular potentials of H 2 S 2 with the rare gases ͑He, Ne, Ar, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
75
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 43 publications
(30 reference statements)
5
75
0
Order By: Relevance
“…Moreover, its simplicity is useful to serve as a prototypical model to the study of line broadening and of the hindered rotation dynamics of molecules, including stereomutation, 8,21,22 control of torsional modes, [23][24][25][26][27] and the spatiotemporal evolution of wave packets. 28 Because of the diversity of applications, a basic point of general interest concerns the role that non-covalent forces and hydrogen bonding play on the thermodynamics of H 2 O 2 and of its structural analogues, namely, molecules with similar skewed structures, [29][30][31][32][33] with varying role of the repulsion between adjacent lone pairs, e.g., hydrogen disulfide, hydrazine, hydroxylamine, diphosphane, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its simplicity is useful to serve as a prototypical model to the study of line broadening and of the hindered rotation dynamics of molecules, including stereomutation, 8,21,22 control of torsional modes, [23][24][25][26][27] and the spatiotemporal evolution of wave packets. 28 Because of the diversity of applications, a basic point of general interest concerns the role that non-covalent forces and hydrogen bonding play on the thermodynamics of H 2 O 2 and of its structural analogues, namely, molecules with similar skewed structures, [29][30][31][32][33] with varying role of the repulsion between adjacent lone pairs, e.g., hydrogen disulfide, hydrazine, hydroxylamine, diphosphane, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work has presented experimental and quantum chemical investigations of the H 2 S‐Rg systems, where Rg is a rare gas 1, 2. Theoretical studies have also considered the H 2 S 2 ‐Rg cases 3, 4. For these systems and their important analogs H 2 O‐Rg 5 and H 2 O 2 ‐Rg 6, correlation with phenomenological formulas has permitted a discussion of the nature of the van der Waals interactions, and of possible further contributions, associated specifically to partial charge transfer and weak hydrogen bonding 7.…”
Section: Introductionmentioning
confidence: 99%
“…For these systems and their important analogs H 2 O‐Rg 5 and H 2 O 2 ‐Rg 6, correlation with phenomenological formulas has permitted a discussion of the nature of the van der Waals interactions, and of possible further contributions, associated specifically to partial charge transfer and weak hydrogen bonding 7. For molecular dynamics studies, in particular for the quantum mechanics ones (possibly requiring freezing of some degrees of freedom inactive in specific problems) we propose here representations of potential energy surfaces, extending to H 2 S 2 ‐Xe an expansion in terms of hyperspherical harmonics previously used for the other rare gases 4. The expansion treats as rigid the intermolecular bonds, but includes flexibility in the torsional mode, as of perspective use in the modeling of chirality changing mechanisms due to molecular collisions 4, 8–18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations shown that oriented chiral molecules can give different results according to their mirror forms. Enantiospecific processes were predicted by molecular dynamics simulations of elastic collisions between oriented H2O2 and H2S2, some of the simplest chiral molecules 15 (for the characterization of the potential energy surfaces with rare-gas-atoms see references [16,17]). Vector correlation also shown that the photodissociation by linearly polarized radiations of oriented chiral molecules can lead to different angular distributions of photofragments according to specific enantiomer.…”
Section: Introductionmentioning
confidence: 99%